Historical aspects and modern concepts in the treatment of patients with differentiated thyroid cancer, refractory to radioactive iodine therapy - E. V. Borodavina; V. V. Krylov; P. A. Isaev; A. Yu. Shurinov; A. A. Rodichev (Опухоли головы и шеи)
Radioiodine therapy for differentiated thyroid cancer has been used for a long time, mainly in patients of intermediate and high risk, as well as in the presence of distant metastases. However, about 30–40 % of patients are refractory to radioiodine therapy, which significantly worsens the prognosis. In patients with radioiodine-refractory differentiated thyroid cancer, therapy with targeted agents, primarily tyrosine kinase inhibitors, is indicated.This review addresses the criteria for refractoriness and criteria for prescription of targeted therapy, and presents the results of clinical studies of the targeted agents used. As of today, lenvatinib is the most well-known targeted agent. In particular. In SELECT trial lenvatinib demonstrated efficacy in terms of progression-free survival and overall survival in patients with radioiodine-refractory differentiated thyroid cancer. As a result, lenvatinib was included in the international and Russian clinical guidelines for the management of this group of patients as a drug of the 1st line of targeted therapy.